Intricate Regolith Reworking Processes Revealed by Microstructures on Lunar Impact Glasses. Issue 12 (15th December 2022) - Yan, Pan; Xiao, Zhiyong; Wu, Yunhua; Yang, Wei; Li, Jin‐Hua; Gu, Li‐Xin; Liao, Shiyong; Yin, Zongjun; Wang, Hao; Tian, Heng‐Ci; Zhang, Chi; Wu, Suping; et al.
Abstract: Glasses cooled from impact melt and vapor are a common component in lunar regolith, carrying important information about protolith composition, regolith formation, and impact flux on the Moon. Interpretations, however, are frequently challenged due to widespread ambiguity in determining their provenances. Regolith samples returned by China's Chang'E‐5 mission provide a unique opportunity to study the microscopic mechanism of regolith reworking on the Moon, because as evidenced by the coherent radioisotope ages and petrographic characteristics of basaltic clasts in the regolith, the Chang'E‐5 regolith was mainly evolved from local mare materials, containing minor exotic components. Here, we report 153 glass particles larger than 20 μm in diameters that were screened from 500 mg of Chang'E‐5 regolith. Most glass particles have rotational shapes and contain structural and/or compositional heterogeneities in interiors, and geochemical analyses reveal a dominant origin as impact melt of local mare materials. Surfaces of the impact glasses are observed to have abundant protruded and dented microstructures, which are classified as different groups based on their morphology and geochemistry. Similar microstructures were observed on impact spherules collected by the Apollo and Luna missions, but those on the Chang'E‐5 impact glasses were formed without substantial involvement of exotic ejecta. Microstructures such as silicate melt pancakes that frequently exhibit flow spikes at margins, nano‐phase iron‐rich mounds that are arranged with semi‐equidistant spaces in curves and patches, spatially clustered microcraters that are indicative of secondary impacts, and blunt linear scratches with terminal particles all suggest that regolith reworking mainly occurred among local materials at low speeds. Plain Language Summary: Regolith particles on the Moon exhibit an abundance of small‐scale surface texture or microstructures that were formed during regolith reworking. Lunar impact glasses are mainly melted from surface regolith, and microstructures on their surfaces record the history of subsequent regolith reworking. The possible contribution of exotic ejecta in regolith gardening is an interesting topic in lunar science. However, resolving this issue has been a persistent difficulty by both remote observations and sample analyses. China's Chang'E‐5 mission returned regolith samples from one of the youngest mare units on the Moon, and earlier sample analyses revealed little exotic components. In 500 mg of Chang'E‐5 regolith, we handpicked 153 glass particles that are larger than 20 μm. Most of the particles are heterogeneous impact glasses that contain voids and unmelted fragments, and geochemical analyses showed that the remaining structurally homogeneous particles were also impact glasses formed from local regolith. Based on high‐resolution microscopic imaging and elemental mapping, we recognized and classified the abundant protruded and dented microstructures on the glass particles. Morphology and crosscutting relationship of the microstructures suggest that they were mostly formed during regolith reworking by low‐speed events of local materials that had various thermophysical states (vapor, melt, and solid). Key Points: 153 glass particles larger than 20 μm in diameters are separated from 500 mg of Chang'E‐5 regolith Crosscutting relationships among surface microstructures reveal intricate regolith reworking processes Protruded and dented microstructures on surfaces of Chang'E‐5 glass particles were formed with velocities lower than primary impacts